Intrapreneurship versus independent entrepreneurship: A cross-national analysis of individual entrepreneurial behavior - Niels S. Bosma; Erik Stam; S. Wennekers (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2011)
This paper presents the results of the first international comparative study of intrapreneurship and independent entrepreneurship. The prevalence of intrapreneurship is about twice as high in high income countries as in low income countries. We find that at the individual level, intrapreneurs are much more likely to have the intention to start a new independent business than other employees. However, there is a negative correlation between intrapreneurship and early-stage entrepreneurial activity at the macro level. One explanation for these contrasting outcomes is the diverging micro level effect of education on intrapreneurship (positive effect) and early-stage entrepreneurial activity (negative effect).
Keywords: 330; intrapreneurship; comparative entrepreneurship; economic development; industrial organization; multi-level analysis